O espelho e a janela: as investigações ópticas de Filippo Brunelleschi (1377-1446) e Leon Battista Alberti (1404-1472) para a "costruzione legittima" - Camelo, Midori Hijioka (2009)
This work tried to identify the contributions of Filippo Brunelleschi and Leon Battista Alberti to the geometrical optics study. Tradicinally, seen by the history of arts and architecture study as inventors of the perspective, in this history of science study, the issue of genealogy was left behind, so they could find in the investigations about costruzione legittima , contributions for the geometrical optics. The period lived by Brunelleschi and Albert, the Renaissance one, shows many changing elements that made the transition from the Medieval and the Modern History. Specially about the perspective study, it s an incorporating moment, with a different meaning to the word. What used to be the synonym of optics throughout Middle Age, thanks largely to the investigations of architects and painters started then, has now the idea of the representation way , keeping it though the time, like we understand it today. Along with the complex movement of approaching of the heavenly thing to the ones here on Earth, witch in canvas mean the introduction of elements of the real world in representations, we can also see an approach of mathematics to the useful things of life, and geometry becomes equally important to the costruzione legittima of visual reality. In the arts and science knowledge and duties meetings, brought to you by the humanism, the spirit of modern science blends together, In the history of geometrical and experimental optics, the art of painting is show more present than it was traditionally thought to. At the time of seeing, the birth of modern science, the connections of Brunellesch and Alberti revealed how artificial the limit of art and science, the duties and the knowledge